PROFESSIONAL COMPETENCIES AND ETHICAL ASPECTS OF NURSING CARE IN THE OPERATING ROOM (International journal of artificial intelligence, 2025)
This review article is devoted to the analysis of professional competencies and ethical aspects of nursing care in the operating room. The study examines modern approaches to organizing the work of an operating room nurse, her key functions, and her responsibilities as part of the surgical team. Particular attention is paid to adherence to the principles of medical ethics, ensuring patient safety, and maintaining a high level of professional culture. The review summarizes domestic and international data reflecting the requirements for the knowledge, skills, and personal qualities of an operating room nurse. The importance of continuous professional education, as well as the development of communication and stress-resilience skills that ensure the quality and ethical integrity of surgical nursing care, is emphasized.